Bioelectric phase angle and its relationship with indicators of body composition in children - O.S. Palamarchuk; O.M. Horlenko; Ya.I. Slyvka; O.A. Rishko; M.A. Derbak (Zaslavsky O.Yu., 2024)
Background. The issue of sarcopenia is becoming increasingly relevant for children, yet its relationship with phase angle (PA) of bioimpedance analysis remains incompletely understood. Objective: to investigate the relationship between phase angle and body composition in children aged 8 to 14 years. Materials and methods. Data from bioimpedance analysis, correlation, and regression analysis were utilized. Results. During the study, it was found that in girls, PA correlates with body fat (BF) and skeletal muscle (SM and sarcopenic index (SI)) content, with correlation coefficients of 0.36, 0.43, and 0.34, respectively. Additionally, regression analysis showed that SI plays a significant role in determining PA in girls, explaining 18.18 % of the variance. In boys, a positive correlation between PA and SI was also observed, with a correlation coefficient of 0.63, and SI played a key role in determining PA, explaining 40.39 % of the variance. It was also found that SM content has a weaker but statistically significant impact on PA in both genders, explaining 14.70 % of the variance in girls and 7.17 % in boys. Total body mass also showed a weak but statistically significant correlation with PA in girls and boys. Further analysis revealed that the relationship between PA and body composition was significant, particularly in the H-L plane, where PA was more dependent on skeletal muscle content, indicating the importance of considering this parameter when assessing the physiological status of children's bodies. Conclusions. The results of this study underscore the importance of phase angle as a marker for assessing body composition in children. The identified positive association between PA and body composition suggests a potential usefulness of PA in determining sarcopenia and musculoskeletal health. For further clinical use of PA in clinical practice, standardization of measurement methodology and creation of reference databases are necessary